2019
DOI: 10.1016/j.ajps.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Modulating intestinal mucus barrier for nanoparticles penetration by surfactants

Abstract: Improving peroral delivery efficiency is always a persistent goal for both small-molecule and macromolecular drug development. However, intestinal mucus barrier which greatly impedes drug-loaded nanoparticles penetration is commonly overlooked. Therefore, in this study, taking fluorescent labeled PLGA (poly (lactic-co-glycolic acid)) nanoparticles as a tool, the influence of anionic and nonionic surfactants on mucus penetration ability of nanoparticles and their mucus barrier regulating ability were studied. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The authors postulated that Tween micelles might diffuse through the mucus gel, minimally impacting its structure, and interact with hydrophobic regions of the mucus. More recently, Zhang et al 51 showed that the exposure of the porcine small intestinal mucus to Tween 80 reduced the bulk viscosity of the mucus and facilitated nanoparticle penetration through the mucus. The particulate diffusivity was enhanced to a larger extent after the mucus had been treated with sodium dodecyl sulfate, however the authors did not report on how the exposure to this anionic surfactant influenced the surface charge of diffusing nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The authors postulated that Tween micelles might diffuse through the mucus gel, minimally impacting its structure, and interact with hydrophobic regions of the mucus. More recently, Zhang et al 51 showed that the exposure of the porcine small intestinal mucus to Tween 80 reduced the bulk viscosity of the mucus and facilitated nanoparticle penetration through the mucus. The particulate diffusivity was enhanced to a larger extent after the mucus had been treated with sodium dodecyl sulfate, however the authors did not report on how the exposure to this anionic surfactant influenced the surface charge of diffusing nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…These observations can be explained with the fact that surfactants with a higher tendency to form micelles may also better interact with skin components and induce their perturbation, thus promoting PLGA particles penetration in the wound tissue. Comparable results were reported by Zhang et al, who found that PLGA nanoparticle permeation across mucus and the intestinal barrier could be increased by both ionic (SLS) and non-ionic (Tween 80) surfactants with different degrees of penetration enhancement depending on the surfactant physicochemical properties [ 40 ].…”
Section: Resultsmentioning
confidence: 80%
“…A number of studies have investigated the effects of surfactant on drug and particle penetration across mucus [ 37 , 38 , 39 ]. It was shown that surfactants can modify the mucus by increasing its hydrophilicity and thus particle diffusion across it [ 40 ]. Mucus has a complex composition with electrolytes, lipids, nucleic acids, cell debris, and large glycosylated proteins such as mucin being the main components [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…A modified solvent extraction/evaporation technique was used to prepare AE@NPs ( Kou et al, 2017 ; Zhang et al, 2019 ; Zheng et al, 2020 ). In brief, the appropriate amount of PLGA, DSPE-PEG2000, ALA, and ERL was dissolved in dichloromethane (DCM), and then 1% (v/v) PVA solution was added.…”
Section: Methodsmentioning
confidence: 99%